PERLINDUNGAN HUKUM TERHADAP CALON PENUMPANG YANG MENGGUNAKAN DAUR ULANG ALAT RAPID TEST ANTIGEN COVID-19 DI BANDARA KUALANAMU - Siahaan, Nomensen Freddy (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2021)
The Covid-19 pandemic does bring a variety of phenomena that occurs in the community, ranging from the social, economic, health, and others. One of the phenomena that occurs in the community is in the north Sumatra area. According to the news published, the North Sumatra Regional Police has appointed five employees at PT Kimia Farma Diagnostika as suspects in the case of recycling covid-19 antigen rapid test equipment at Kualanamu Airport.The method which was used in this Scholar Paper was Qualitative Research Method, a kind of Normative Legal Writing which was based on prescriptive library research concerning study of positive law. For the Primary Legal Materials, Scholar used references such as Act Number 8 Year 1999 regarding to Consumer Protection, etc. And for Secondary Legal Material, Scholar uses books, journals, papers, newspapers, and report of legal writing. Then, for Tertiary Legal Materials, Scholar used references such as legal dictionary, dictionary Indonesian-English dictionary and vice versa, etc.Consumer has rights that must be protected from legal perspectives.Â  Law Number 8 of 1999 concerning Consumer Protection Article 1 point (2) states that consumers are every user of goods and or services available in society, whether for the benefit of themselves, family, others, or other living beings and not for trading. It is crystal clear as regulated by our legislation, Consumer Protection must have a guarantee of legal certainty given to consumers in this case is passengers as consumers of covid-19 antigen rapid test equipment recycling does not get guaranteed legal certainty because the Covid-19 antigen rapid test tool they receive is used goods, unhygienic anymore.Try to imagine if the rapid test tool that has been used is used by passengers whose health condition is not good (in a sick condition orcarrying certain viruses or bacteria) and it transmits to the next passenger who uses the recycling of the Covid-19 antigen rapid test tool. No one can guarantee this because it is the act of selling recycling tools rapid test antigen Covid-19 is an illegal act (unlawful or not justified according to the law).Related to this case, the Government should internalize the production and distribution process of the swab tool in order to ensure the quality of its products so as not to defect or used. Moreover, this product is distributed in large quantities and in the pandemic period also so that it must be extra supervision so as not to be misused by irresponsible parties so that points can be met properly.